EVALUATION OF THE ANALYTICAL VALUE OF SARS-CoV-2 ANTIGEN TEST IN RELATION TO Ct-VALUES OF RT-qPCR IN PATIENTS SUSPECTED OF COVID-19 - Popova, Gorica; Boskovska, Katerina; Arnaudova Danevska, Ivana; Blagoevska, Katerina (Македонско лекарско друштво = Macedonian Medical Association, 2021)
Introduction. COVID-19 pandemic threatens global human health. Reverse-transcription quantitative polymerase chain reaction (RT-qPCR) is a reference test for identification of acute SARS-CoV-2 infection, but it is associated with results delay. There is a need of fast and reliable tests which can improve the efforts of controlling the transmission of SARS-CoV-2. Aim. The aim of this study was to determine the analytical value of the rapid SARS-CoV-2 Ag-test in relation to the Ct values of the RT-qPCR. Methods. The study group comprised outpatients suspected for COVID-19, sampled twice, first for the routine RT-qPCR, and second for SARS-CoV-2 antigen testing. The results obtained by the rapid antigen test (Panbio™ COVID-19) were evaluated in relation to Ct values of the SARS-CoV-2 E-gene, obtained by RTqPCR Allplex 19-nCoV multiplex assay platform. Results. SARS-CoV-2 prevalence, based on RT-qPCR, was 50.8% (186/366). Specificity of the PanbioTM COVID- 19 Ag Rapid Test was 100%. Test sensitivity was 73.8%. Restricting RT-qPCR to Ct-values<30 increased test sensitivity to 91.2%. Conclusion. The findings underscored the epidemiological value of the rapid Ag-test since it reliably identifies contagious SARS-CoV-2 infected individuals who actively spread the virus in the community.
ЕВАЛУАЦИЈА НА АНАЛИТИЧКАТА ВРЕДНОСТ НА SARS-CoV-2 АНТИГЕНСКИ ТЕСТ ВО ОДНОС НА Ct ВРЕДНОСТИТЕ НА РТ-ПВР КАЈ ПАЦИЕНТИ СУСПЕКТНИ ЗА КОВИД-19
Keywords: COVID-19; RT-qPCR; rapid SARS-CoV-2 Ag test; sensitivity; specificity